2004
DOI: 10.1097/00002030-200403260-00007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antiretroviral drugs on liver fibrosis in HIV-infected patients with chronic hepatitis C

Abstract: HAART regimens including nevirapine are associated with faster liver fibrosis progression in HIV-infected patients with chronic hepatitis C. In contrast, patients on PI as the backbone of potent antiretroviral therapy are more likely to show less liver fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
4
5

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(109 citation statements)
references
References 23 publications
2
98
4
5
Order By: Relevance
“…25 Moreover, many surveys have failed to find any association between alcohol consumption and liver fibrosis. 24,[32][33][34] In the present study, as in many others, the alcohol consumption calculation was based on the clinical interview. This procedure of estimating daily alcohol intake is very unreliable in alcohol drinkers.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…25 Moreover, many surveys have failed to find any association between alcohol consumption and liver fibrosis. 24,[32][33][34] In the present study, as in many others, the alcohol consumption calculation was based on the clinical interview. This procedure of estimating daily alcohol intake is very unreliable in alcohol drinkers.…”
Section: Discussionmentioning
confidence: 93%
“…23 Finally, some hepatotoxic antiretroviral drugs commonly used in HCV/HIV-coinfected patients, such as nevirapine, may enhance the progression of liver fibrosis. 24 Probably as a consequence of these deleterious effects, HIV carriers showed signs of more severe liver disease, through a poorer Child-Turcotte-Pugh score and MELD score, at the time of the first hepatic decompensation. That notwithstanding, the fact that HIV infection is a mortality predictor independent of the aforementioned scores suggests that the negative impact HIV exerts on the outcome of HCV-related liver disease before the development of decompensated cirrhosis 4,5 is also maintained in ESLD.…”
Section: Discussionmentioning
confidence: 99%
“…Patients should therefore be carefully monitored for hepatotoxicity when highly active antiretroviral therapy (HAART) is commenced or changed. There is some evidence that the risk of early hepatotoxicity with nevirapine and high-dose ritonavir (RTV) (1000 mg/ day) is higher than with other ARTs [38,39] and nevirapine may also be linked to increased liver fibrosis [40], although not all studies show this [41]. High-dose RTV is no longer recommended in ART and low-dose RTV [in doses used to boost other protease inhibitors (PIs)] is not associated with significant liver problems.…”
Section: Antiretroviral Therapy and Hepatotoxicitymentioning
confidence: 99%
“…Conversely, not all patients are equally adherent to HAART. In addition, in some studies protease inhibitor (PI)-based HAART has been found to be associated with a slower rate of liver fibrosis progression than other HAART strategies, 6,7 although this finding has not been confirmed by other researchers. 8,9 Finally, some HIV/HCV-coinfected patients receiving HAART are also given therapy against chronic hepatitis C with interferon plus ribavirin and achieve sustained virological response, which seems to lead to a reduction in the incidence of episodes of decompensated cirrhosis.…”
mentioning
confidence: 97%